Prevalence of dental caries and periodontal disease in a rural area of Faridabad District, Haryana, India - Naseem Shah; Vijay Prakash Mathur; Shashi Kant; Arpit Gupta; Vartika Kathuria; Partha Haldar; Ravindra Mohan Pandey (Wolters Kluwer Medknow Publications, 2017)
An oral health survey was conducted in 829 individuals in different age groups in Ballabhgarh, Haryana, India, to estimate the prevalence of Dental caries and Periodontal diseases. A survey tool was modified from WHO's STEPwise approach to surveillance and Oral Health Assessment form 2013 from recently released WHO Oral Health Survey: Basic Methods (5th Edition) keeping in mind the South East Asian region. Out of 28 villages, six villages were randomly selected. A random list of study participants (Age-sex specific) was generated from the pooled list of these 6 villages. Local health workes helped in inviting the specific subjects to one centralized location within each village/ locality. The subjects were examined by trained dental surgeons and recordings were done by trained assistants. The prevalence of dental caries in 5-7 year, 12-15 year, 35-44 year and 65-74 year was 33.2%, 31.3%, 64.9% and 50.1% respectively. The prevalence of Periodontal Disease in 35-44 year and 65-74 year found to be 65.2% and 90.4% respectively. Only 37 participants had mucosal lesions, of which leukoplakia and tobacco pouch keratosis was seen in majority. Using the adopted tool, the prevalence of dental caries was found to be highest in 35-44 year (64.9%) age group and the prevalence of periodontal disease was found to be high in 35-44 year (65.2%) age group and highest in 65-74 year (90.4%) age group. Oral health promotion efforts are required to prevent oro-dental diseases in the studied population.